Relative growth and morphological sexual maturity of the freshwater crab Trichodactylus fluviatilis Latreille 1828 (Decapoda, Trichodactylidae) from west central Sao Paulo State, Brazil - Pescinelli, Regis Augusto [UNESP]; Farinelli Pantaleao, Joao Alberto [UNESP]; Davanso, Thiago Maia [UNESP]; Costa, Rogério Caetano da [UNESP] (Taylor & Francis Ltd, 2014)
An analysis of relative growth was performed to determine the size at morphological sexual maturity of Trichodactylus fluviatilis Latreille 1828. Samples were collected by trapping at night from January 2010 through June 2011 from the Barreiro River (22 degrees 34 ' 42 '' S; 49 degrees 11 ' 92 '' W), west central Sao Paulo State, Brazil. The following measurements were obtained (mm): carapace width (CW) (independent variable), cheliped propodus length (PL), cheliped propodus height (PH), cheliped propodus width (PW), first pleopod length, and abdomen width (AW). The males showed positive allometry in the juvenile and adult stages for the following relationships: PL vs. CW, PH vs. CW, and PW vs. CW. In the females, a positive allometry was observed for AW vs. CW in the juvenile stage, and a negative allometry was observed for this relationship in the adult stage. The differential growth of the chelipeds in males could be related to territorial conflict and courtship, whereas the changes in the growth of the female abdomen most likely favor higher reproductive success.
Keywords: allometry; reproduction; Brachyura